Worker Education in Overcoming Burnout at Work Cleaning Service at Campus IV Ahmad Dahlan University Yogyakarta - Nur Fitriani; Daeng Dea Nuraini; Shifa Rizqa Zhafira; Rini Afifah Husna; Ratna Hafitri Astutik; Ayu Faradilla Duwila; Machfudz Eko Arianto (PT. Anagata Sembagi Education, 2024)
Burnout is a condition that is often faced by workers due to several factors. The purpose of this study was to provide education about burnout in cleaning services at Campus IV of Ahmad Dahlan University Yogyakarta. The method in this study is observation by conducting a pretest post test and providing counseling material with a lecture method on burnout and using poster media as a promotional tool followed by discussion and question and answer. The material provided is related to how to overcome burnout at work, the population in this study is cleaning service at Campus IV Ahmad Dahlan University Yogyakarta with a sample of 10 cleaning service people. The results of the study found that there were workers who experienced increased knowledge or understanding of how to overcome burnout at work. However, there are some employees or workers whose scores decreased after taking the post test.